2017
DOI: 10.1155/2017/3428236
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Interleukin-22 Gene Confer Predisposition to Autoimmune Thyroid Disease

Abstract: As there are no previous studies on the interleukin-22 (IL-22) variants in autoimmune thyroid disease (AITD), the present study aimed to explore the association between polymorphisms of IL-22 and the predisposition to AITD. The study had 975 AITD patients, including 639 Graves' disease (GD) and 336 Hashimoto's thyroiditis (HT) individuals and 851 healthy cohorts. Ligase detection reaction (LDR) and direct sequencing method were used for genotyping the IL-22 gene polymorphisms at rs2046068, rs2227478, rs2227485… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…They together form a large family called IL-10 family [17]. We know now that polymorphisms of the genes of IL-10, IL-22, and IL-28 are associated with a higher prevalence of autoimmune thyroid disease [18][19][20]. Until the present study was conducted, only one research aimed to evaluate the role of IL-29 in thyroid disorders.…”
Section: Introductionmentioning
confidence: 97%
“…They together form a large family called IL-10 family [17]. We know now that polymorphisms of the genes of IL-10, IL-22, and IL-28 are associated with a higher prevalence of autoimmune thyroid disease [18][19][20]. Until the present study was conducted, only one research aimed to evaluate the role of IL-29 in thyroid disorders.…”
Section: Introductionmentioning
confidence: 97%
“…They found the polymorphisms of CD40 and FCRL3 were associated with GD and the polymorphisms of ZFAT were associated with HT, which demonstrated that multiple genes could be common to both diseases and some were unique. In the last few years, more and more AITDs susceptibility genes and loci have been discovered, such as AITDs with rs6479778 (located within the ARID5B gene); GD with rs12147587 (located within the NRXN3 gene) and rs2284720 (located within TSHR genes) [12]; HT with rs7537605 (located within the VAV3 gene) [13]; AITDs with polymorphisms of TRAF1 [14] and Interleukin-22 [15]. In short, identifying more important genes and loci of AITDs is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al also showed an elevated rs2046068 AA genotype in the control group in contrast to a group with autoimmune thyroid disease (AITD), Graves' disease (GD), and Hashimoto's thyroiditis (HT). However, the relationship was not statistically significant [36]. We found that the rs2046068 A allele in the IL-22 gene was statistically high under a dominant mode of inheritance in the malaria group within the 1-5 years age group compared to the 6 years and older age group.…”
Section: Discussionmentioning
confidence: 53%